Motor and Limbic System Contribution to Emotional Laughter across the Lifespan. (17th December 2019) - Talami, Francesca; Vaudano, Anna Elisabetta; Meletti, Stefano
Abstract: Laughter is a universal human behavior generated by the cooperation of different systems toward the construction of an expressive vocal pattern. Given the sensitivity of neuroimaging techniques to movements, the neural mechanisms underlying laughter expression remain unclear. Herein, we characterized the neural correlates of emotional laughter using the onsets and the duration of laughter bursts to inform functional magnetic resonance imaging. Laughter-related blood oxygen level-dependent (BOLD) increases involved both the motor (motor cortex, supplementary motor area, frontal operculum) and the emotional/limbic (anterior cingulate cortex, amygdala, n. accumbens, hippocampus) systems, as well as modulatory circuitries encompassing the basal ganglia, thalamus, and cerebellum. BOLD changes related to the 2 s preceding the laughter outbreak were selectively observed at the temporo-occipital junction and the periaqueductal gray matter, supporting the role of the former in the detection of incongruity and the gating role of the latter in the initiation of spontaneous laughter. Moreover, developmental changes were identified in laughter processing, consisting in a greater engagement of the reward circuitry in younger subjects; conversely, the default mode network appears more activated in older participants. Our findings contribute valuable information about the processing of real-life humorous materials and suggest a close link between laughter-related motor, affective, and cognitive elements, confirming its complex and multi-faceted nature.